Essential oils from Homalomena aff. pendula (Blume) Bakh F. and Its Antioxidant Activities - Rifaldi Harfiyantama; Nurainas Nurainas; Deddi Prima Putra; Nova Syafni (Fakultas Farmasi Universitas Andalas, 2026)
Homalomena is a genus from the family Aracaceae that is characterized by scent. Most Homalomena species from Indonesia have limited information on the chemical components of their essential oils, including those found in West Sumatra Province. The species of Homalomena aff. pendula (Blume) Bakh. F. is found in large amounts in Padang city, and it has the potential to explore its profile of essential oil substances in its leaves, petioles, and rhizomes. In this research, the antioxidant activity of the essential oils was screened using three methods: DPPH, ABTS, and FRAP. The essential oils are extracted through hydro-distillation, and their components are analyzed using Gas Chromatography-Mass Spectrometry (GC-MS). The results show that the three major components in the leaves and petioles were β-bisabolene, α-selinene, and α-bergamotene with different percentages. The rhizomes had the same higher component as β-bisabolene, followed by trans-caryophyllene and α-bergamotene. The antioxidant activity, as measured by DPPH and ABTS, showed an IC50 greater than 200 μg/mL. That result is also supported by the FRAP value of leaves, petioles, and rhizomes, 0.165±0.0081; 0.168±0.0019; 0.191±0.0003 µmol Fe(II)/mg sample and 0.013±0.0006; 0.014±0.0001; 0.015±0.0001 µmol trolox/mg sample, respectively. Although the essential oils from H. aff. pendula do not exhibit antioxidant activity, the primary compound, β-bisabolene, has been shown to possess other potential activities.